Pengembangan Media Pembelajaran Puzzle dalam Pembelajaran Kosakata Berbasis Quantum Learning - Ida Farida; Yuyun Rohmatul Uyuni (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2022)
Students consider Arabic vocabulary to be very difficult to understand, as is the case with pupils at the Islamiyah Islamic Secondary School. Students find it difficult to understand Arabic vocabulary because the use of the educational method is not appropriate in the learning process. This research aims to: 1) To know the process of teaching vocabulary in the seventh grade at the Islamic intermediate school. 2) To know the puzzle teaching aid is developed in teaching vocabulary on the basis of Quantum Learning. 3) To know the effectiveness of developing the puzzle educational tool in teaching vocabulary on the basis of Quantum Learning. 4) To know the advantages and disadvantages of developing the educational puzzle in teaching vocabulary on the basis of Quantum Learning. To achieve the above-mentioned goals, the researcher developed the puzzle educational tool using the development theory of Borg and Gall in seven steps. And the results of expert evaluation of the medium, where experts provide the evaluation of the educational medium in terms of material quality and material content with a value of a factor of 1 which, if described, has a very high validity. The average value of the pre-test is 61%, and the average value of the post-test is 81,4%. The significance value of the data is 0.00. It is known that if the significance value is less than 0.05, HO will be rejected and both data have significance.